2022
DOI: 10.1108/ijoa-03-2022-3207
|View full text |Cite
|
Sign up to set email alerts
|

How business strategy drives human resource practices in small and medium enterprises? Evidence from Pakistani autoparts industry

Abstract: Purpose In large enterprises, the notion is that an organization’s business strategy is a significant determinant of its human resource (HR) practices. However, there is limited evidence in the literature of such linkages for small and medium enterprises (SMEs). The purpose of this paper is to examine the nature and extent of the relationship between the types of business strategies used and HR practices, namely, staffing, training and employee relations among SMEs. Design/methodology/approach The authors ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 83 publications
(126 reference statements)
0
4
0
2
Order By: Relevance
“…Ahmad and Khan (2023) expand previous research with a two-part study of SMEs operating in Pakistan’s autoparts manufacturing sector. Such companies serve major automobile assemblers, mainly in the shape of leading Japanese companies.…”
Section: Some Evidence From Pakistanmentioning
confidence: 75%
“…Ahmad and Khan (2023) expand previous research with a two-part study of SMEs operating in Pakistan’s autoparts manufacturing sector. Such companies serve major automobile assemblers, mainly in the shape of leading Japanese companies.…”
Section: Some Evidence From Pakistanmentioning
confidence: 75%
“…Conversely, in southern Italy, companies in regions with lower employment density have lower training opportunity costs (Filippetti et al, 2019), which stimulates investment in training. Ahmad and Khan (2022) pointed out that human resource practices, including training, differ considerably between companies operating in risky and less developed market environments and competitive industries that use a more skilled workforce. A disadvantage of training incentives is the low level of support from local stakeholders, such as chambers, associations, or local authorities, concerning the training needs of companies (Fuchs et al, 2021).…”
Section: Industry-level Factorsmentioning
confidence: 99%
“…Furthermore, Tam & Gray (2016) found that three out of four learning levels (individual, group, organizational, and interorganizational) practiced in MSMEs varied in importance between life cycle stages. There is significant potential to be realized through the strategic management of HR practices to achieve a sustainable competitive advantage (Ahmad & Khan, 2022). Here, supervisory and management education and appropriate workforce skill levels along with continuous industry-leading training appear to be the most successful business strategies followed by MSMEs.…”
Section: Human Resources Strategymentioning
confidence: 99%